2004
DOI: 10.1074/jbc.m404603200
|View full text |Cite
|
Sign up to set email alerts
|

Self-protection Mechanism in d-Cycloserine-producing Streptomyces lavendulae

Abstract: An antibiotic, D-cycloserine (DCS), inhibits the catalytic activities of alanine racemase (ALR) and D-alanyl-D-alanine ligase (DDL), which are necessary for the biosynthesis of the bacterial cell wall. In this study, we cloned both genes encoding ALR and DDL, designated alrS and ddlS, respectively, from DCS-producing Streptomyces lavendulae ATCC25233. Each gene product was purified to homogeneity and characterized. Escherichia coli, transformed with a pET vector carrying alrS or ddlS, displays higher resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…This observation means that the conversion of DCS to a final form, which noncompetitively inhibits the enzymatic activity, is significantly slow in Streptomyces ALR, resulting in the resistance to DCS (34). In the crystal structure of the DCS-bound form of the Streptomyces ALR, the C␣ atom of the final DCS-derivative in site A is located near the hydroxyl of Tyr 270 Ј, whereas that in site B is near the amino group of Lys 38 .…”
Section: The Active Site Around the Plp Derivative In Dcs-and Lcs-boumentioning
confidence: 99%
See 3 more Smart Citations
“…This observation means that the conversion of DCS to a final form, which noncompetitively inhibits the enzymatic activity, is significantly slow in Streptomyces ALR, resulting in the resistance to DCS (34). In the crystal structure of the DCS-bound form of the Streptomyces ALR, the C␣ atom of the final DCS-derivative in site A is located near the hydroxyl of Tyr 270 Ј, whereas that in site B is near the amino group of Lys 38 .…”
Section: The Active Site Around the Plp Derivative In Dcs-and Lcs-boumentioning
confidence: 99%
“…Crystallography of Streptomyces ALR-Enzyme expression and purification of the Streptomyces ALR were done as described previously (34). Prior to crystallization, the purified enzyme solution was dialyzed against a 30 mM Tris-HCl buffer (pH 8.5) containing 50 mM NaCl and 0.5 mM PLP and then concentrated to 10 mg/ml using an Amicon concentrator (Millipore).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The functions of dcsI and dcsJ had previously been analyzed using the corresponding genes cloned from other D-CS-producing strains, i.e., S. lavendulae ATCC 25233 (11) and S. garyphalus (CSH) 5-12 (12), demonstrating that both gene products are responsible for self-resistance in the D-CS producer. Gene disruption and recombinant protein analyses have demonstrated that the revised D-CS biosynthetic pathway is as follows.…”
mentioning
confidence: 99%